Effects of a Change from an Indoor-Based Total Mixed Ration to a Rotational Pasture System Combined With a Moderate Concentrate Feed Supply on Rumen Fermentation of Dairy Cows - Julia Hartwiger; Melanie Schären; Sarah Potthoff; Liane Hüther; Susanne Kersten; Dirk von Soosten; Andreas Beineke; Ulrich Meyer; Gerhard Breves; Sven Dänicke (Animals, 2018)
In spring, transition from a total mixed ration (TMR) to pasture requires rumen adaptions for the cow. It had been shown that transition period does not necessarily mean an increased risk for subacute ruminal acidosis (SARA). After adaption to pasture, however, supplying low amounts of concentrate did indicate increased risk, but caused no adverse effects on rumen morphology and absorption capacity. The present study aimed to investigate the effect of transition, and how a supply of 4.5 kg dry matter concentrate·cow−1 <semantics> · </semantics> day−1 during fulltime grazing influenced different rumen parameters. During a 12-week trial eleven rumen-cannulated dairy cows were observed during transition from confinement to pasture (PG; n = 6) and compared to cows fed TMR indoors (CG; n = 5). The CG stayed on a TMR based ration (35% corn silage, 35% grass silage, 30% concentrate; dry matter basis), whereas the PG slowly switched to a pasture-based ration (week 0 and 1 = TMR, week 2 = TMR and 3 h pasture·day−1, week 3 and 4 = TMR and 12 h pasture·day−1, and week 5 to 11 = pasture combined with 4.5 kg DM concentrate <semantics> · </semantics> cow−1·day−1). Papillae surface area decreased during transition and increased again during fulltime grazing, while the fractional absorption rate of volatile fatty acids (VFA) was not influenced. This suggests only a limited effect of papillae surface area on VFA absorption rate. Feeding changes resulted in different fermentation profiles of VFA. Changing ratio of starch to sugar during transition to fulltime grazing plus concentrate supply did not lead to lower rumen pH. In conclusion, the concentrate supply combined with high fermentable grass during fulltime grazing increased papillae surface area but did not affect absorption rate or rumen pH, so that risk for SARA was not increased.